Magnetism and quantum criticality in intermetallic compounds RNiSi3 based on rare earths : experiments and simulations (2022)
ABSTRACT: RNiSi3 (R=Gd-Yb) series have exhibited a wide variety of physical phenomena including antiferromagnetism, magnetic hysteresis accompanied by metamagnetic transitions, complex magnetic phase diagrams, coexistence of RKKY interaction and Kondo effect, among others. The combined effect between some of them constitutes a great challenge to comprehend their fundamental interactions. This thesis is the result of trying to understand such interactions in YNiSi3 , LuNiSi3 , Gd1−xYxNiSi3, Tb1−xYxNiSi3 and YbNiSi3−xGex from two different approaches: electronic structure calculations where we employ first-principles DFT, and an experimental focus where we grow single crystals via Sn-flux method and characterize them from X-ray diffraction, magnetization, specific heat and resistivity measurements. As a result of this investigation, we observe that YNiSi3 and LuNiSi3 are non-conventional type-I superconductors at Tc = 1.36(3) and 1.61(2) K, respectively, categorized as anisotropic three-dimensional metals with multiband superconducting ground states in the weak-coupling regime. Moreover, their Cooper pairs are formed by the coupling of Y(Lu), Ni d with Si p electrons. On the other hand, Y-dilute antiferromagnetic systems in which a reduction of the RKKY interaction is expected, lead to other physical manifestations such as the emergence of Ni magnetic moment. This causes competition between ferromagnetic and antiferromagnetic interactions that are evidenced as anomalies above TN in Tb0.5Y0.5NiSi3, or they generate the exchange bias effect in Gd0.50Y0.50NiSi3 and Gd0.35Y0.65NiSi3. Finally, initial studies on quantum criticality in YbNiSi3−xGex antiferromagnetic-Kondo lattice indicate that the strong competition between the RKKY and Kondo interactions allow only a weak change of the ground state of the systems toward fluctuating valence systems.